1981
DOI: 10.1002/bms.1200080604
|View full text |Cite
|
Sign up to set email alerts
|

Comparative electron impact, chemical ionization and field desorption mass spectra of some thioether metabolites of acetaminophen

Abstract: The mass spectra of several thioether conjugates of the widely used analgesic, acetaminophen (4'-hydroxyacetanilide), have been recorded under various ionization conditions. Conjugates were obtained from both in vitro and in vivo sources and purified by high performance liquid chromatography. Some standards were chemically synthesized. Of the thioethers examined, only the methylthio and mercapturic acid conjugates provided parent ions under electron impact conditions. In the chemical ionization mode, using iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The identification and quantitative analysis of GSH conjugates has advanced dramatically as new analytical techniques become available 15. Due to its chemical and thermal instability and high polarity, a GSH conjugate requires extensive derivatization for gas chromatography/mass spectrometric analysis16 and does not produce a molecular ion in direct chemical ionization mass spectrometry 17. Characterization by fast‐atom bombardment or plasma desorption mass spectrometry gives reliable molecular weight information but few diagnostic fragments 18–20.…”
mentioning
confidence: 99%
“…The identification and quantitative analysis of GSH conjugates has advanced dramatically as new analytical techniques become available 15. Due to its chemical and thermal instability and high polarity, a GSH conjugate requires extensive derivatization for gas chromatography/mass spectrometric analysis16 and does not produce a molecular ion in direct chemical ionization mass spectrometry 17. Characterization by fast‐atom bombardment or plasma desorption mass spectrometry gives reliable molecular weight information but few diagnostic fragments 18–20.…”
mentioning
confidence: 99%
“…The molecular ion M + at m/z 456 of 3-glutathionylacetaminophen was not observed in an EI spectrum, and only a low-intensity ion at m/z 411 was observed under CI conditions, corresponding to the loss of formic acid from an MH + ion. In contrast, the FD mass spectrum exhibited an intense protonated molecular ion [M + H] + at m/z 457 together with a prominent [M + Na] + ion at m/z 479 (Nelson et al, 1981). The FD/CID spectrum exhibited a number of additional product ions that resulted from fragmentation of the acetamido group of the parent drug and of bonds in the cysteinyl and g-glutamyl residues (Nelson et al, 1981).…”
Section: Standalone Msmentioning
confidence: 88%
“…The FD technique was developed primarily by Beckey and co-workers (Beckey, 1969) and is considered a forerunner of the ''spray'' techniques in that it involves the application of a high electric field to a liquid surface resulting in the production of intact molecular ions from non-volatile samples. A comparative investigation by Nelson et al (1981) clearly demonstrated the advantage of ''soft ionization'' techniques in offering molecular weight information of the Figure 1. Evolution of key LC/MS technology and its application in drug metabolite identification in the past 50 years.…”
Section: Standalone Msmentioning
confidence: 97%
“…The serial methylsulfonyl pathway for xenobiotic metabolism has been studied in numerous laboratories for numerous compounds such as the drugs cafffeine (1), bromazepam (2), bromovalerylurea (3), acetoaminophen (4), alfoqualone (5), and 3-hydroxyxanthine (6); pesticides and fungicides, including propachlor (7), napthalene (8), (9) and PCNB (10); and pollutants such as DDE (11), PCBs (11)(12)(13), HCB (14) and monochlorodibenzo-p-dioxin (15). During the time that xenobiotic thioether derivatives were discovered, precursors including glutathione, cysteinylglycine, cysteine and N-acetylcysteine (mercapturic acid) conjugates (2,4,5,7,14) have been reported. Furthermore, it is believed that serial methylsulfonyl metabolites might be discovered by more detailed analysis.…”
Section: Introductionmentioning
confidence: 99%